Healthy soil, healthy food, healthy people: An outline of the H3 project. Issue 4 (17th November 2021) - Jackson, Peter; Cameron, Duncan; Rolfe, Stephen; Dicks, Lynn V.; Leake, Jonathan; Caton, Sam; Dye, Louise; Young, William; Choudhary, Sonal; Evans, David; Adolphus, Katie; Boyle, Neil
Abstract: This paper provides an outline of a new research project, funded through UKRI's 'Transforming UK food systems' programme. The H3 project ( Healthy soil, Healthy food, Healthy people ) aims to transform the UK food system 'from the ground up', through an integrated programme of research at lab, farm, landscape, local, regional and national scales. This article introduces the H3 project with a particular emphasis on those parts of our work that have most direct relevance in terms of improving human diet and nutrition. Specifically, we seek to make early interventions in the food system through biofortification and other measures that reduce the need for costly interventions at later stages. Focusing on low‐income populations and using a 'health by stealth' approach, we also seek to increase fibre consumption among the UK population by reformulating foods that are already an established part of people's diet. The paper concludes by assessing the likely impact of these interventions and the significance we attach to working with stakeholders in business, government and civil society.